Comparative Analysis of the Impact of FPO on Paddy Farmers through Canonical Correlation Analysis - Pujitha, Adapa Shalini; Naik, Akkamahadevi; Kumar, Ashok; Biswas, Tufleuddin (Indian Journal of Extension Education, 2024)
This study was conducted in 2023-24 in Srikakulam and Vizianagaram districts of Andhra Pradesh and examines the significant impact of Farmer Producer Organizations (FPOs) on paddy farmers’ income, productivity, and sustainability in the study area. Canonical correlation coefficients analysis was used to identify the connection between independent variables and dependent variables for FPO members and non-members. For FPO members, the maximum canonical correlation was found between the first pair of variates (0.789), with strong relations indicated by Wilks statistics and Eigen values. Key influencing factors for FPO members included scientific orientation, awareness about FPOs, social participation, and innovativeness. In contrast, for non-FPO members, educational and occupational status was significant, with the highest canonical correlation at 0.840. The findings suggest FPOs are critical in enhancing agricultural productivity and farmer well-being, providing valuable insights for policymakers and stakeholders. Addressing these key elements may lead to targeted interventions, fostering sustainable agricultural development and improving rural livelihoods.
Keywords: Canonical correlation analysis; Farmers; producer organization; Knowledge; Productivity